Fibrous Displasia - Helmi Ismunandar; Rani Himayani; DIMAS Arrohmansyah (Medula, 2021)
Fibrous dysplasia is a benign intramedullary fibro-oseus lesion. Fibrous dysplasia occurs from the post-zygotic somatic activation (gain-of-function) mutation in GNAS, which encodes the G-protein associated with the AMP pathway, Gsα. Involvement of the skin, bone, and endocrine system is consistent with mutation events early in embryogenesis, which occur prior to differentiation of the 3 embryonic layers. The diagnosis can only be made after a thorough evaluation of the degree of skeletal disease that is monostotic / polyostotic and the presence of extra-skeletal manifestations. Monostotic fibrous dysplasia is defined as the presence of fibrous dysplasia at only one skeleton site. Polyostotic fibrous dysplasia is defined as the presence of fibrous dysplasia at more than one skeletal site without extra-skeletal manifestations. Examination can be done with plain radiographs or CT scans which are useful for determining the direction of malignancy. Lifestyle optimization is the main target of fibrous dysplasia therapy. Medical treatment is recommended to reduce pain, stabilize lesions, and support bone structures to avoid fractures. While surgical therapy is preferred in treating deformities, to avoid pathological fractures, and to treat symptomatic lesions. Malignant transformation in FD is very rare but routine follow-up should be done.